Aberrant Drug‐Related Behavior Observed During a 12‐Week Open‐Label Extension Period of a Study Involving Patients Taking Chronic Opioid Therapy for Persistent Pain and Fentanyl Buccal Tablet or Traditional Short‐Acting Opioid for Breakthrough Pain. Issue 8 (25th March 2014) - Passik, Steven D.; Narayana, Arvind; Yang, Ronghua
Abstract Objective Evaluate aberrant drug‐related behaviors in patients administering fentanyl buccal tablet or traditional short‐acting opioids for breakthrough pain. Design Twelve‐week open‐label extension. Setting Forty‐two US sites. Subjects Opioid‐tolerant patients with chronic pain who completed the previous randomized, double‐blind, crossover portion of a study comparing fentanyl buccal tablet and immediate‐release oxycodone for treatment of breakthrough pain. Methods Patients were rerandomized to continue treatment with fentanyl buccal tablet or begin any traditional short‐acting opioid. Assessments included Screener and Opioid Assessment for Patients with Pain‐Revised (SOAPP‐R) at baseline and Addiction Behaviors Checklist and Current Opioid Misuse Measure at baseline and final visit. Case report forms were reviewed retrospectively to identify aberrant drug‐related behaviors. Results One hundred thirty patients entered the open‐label extension (fentanyl buccal tablet, N = 65; traditional short‐acting opioid, N = 65). SOAPP‐R scores were <18 (low risk of aberrant drug‐related behavior) in 74% of patients; no significant differences in SOAPP‐R scores were observed between treatment groups. At the final visit, ≤14% of patients in each treatment group had scores indicating potential aberrant drug‐related behavior (Addiction Behaviors Checklist ≥3, Current Opioid Misuse Measure ≥9); no significant differences in scores were observed between treatment groups. Baseline SOAPP‐R score ≥18 was not predictive of Addiction Behaviors Checklist ≥3 but was predictive of Current Opioid Misuse Measure ≥9. Aberrant behaviors were identified in 12 (18%) fentanyl buccal tablet patients and 13 (20%) traditional short‐acting opioid patients. Conclusions Incidence of aberrant drug‐related behaviors was similar between patients taking fentanyl buccal tablet and traditional short‐acting opioids over 12 weeks.